Analisis Risiko Kerentanan Sosial Dan Ekonomi Bencana Longsorlahan Di Kecamatan Kandangan Kabupaten Temanggung - Muawanah, Afi; , Dr.Kuswaji Dwi Priyono, M.Si (2016)
Landslide is one of the many types of natural disasters inflict casualties and material losses. Social and economic aspects is one of the significant aspects of the landslide affected. The purpose of this research is to analyze the distribution of the risk of economic vulnerability and social vulnerability on Kandangan subdistrict and analyze the relationship of social and economic vulnerability against level of the landslide hazard on Kandangan subdistrict. The research method used quantitative - qualitative methods with field survey. Quantitative methods using secondary data analysis and weighting. Qualitative method by analyzing the results to find out the relationship of the level of vulnerability to the extent of the danger of landslides. The results of field survey data was used to strengthen the analysis of secondary data processing results. The methods used for sampling is a method of stratified random sampling or stratified random sampling. The end result obtained is the risk analysis of socio-economic vulnerability in Kandangan Subdistrict. The risk of social vulnerability in Kandangan Subdistrict is dominated with the medium and low levels which indicates that the level of vulnerability to social risk quite well. The risk of economic vulnerability in the south is low vulnerable, but the north side is a very high vulnerable.